2008
DOI: 10.1016/j.molimm.2008.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The interleukin-1 receptor associated kinase 1 contributes to the regulation of NFAT

Abstract: IRAK-1 is a critical modulator regulating innate immunity signaling processes. However, the physiological substrates for IRAK-1 remain poorly defined. In this report, we have demonstrated that IRAK-1 is a kinase responsible for the constitutive phosphorylation and inactivation of the Nuclear Factor of Activated T-cell (NFAT). Expression of IRAK-1 suppressed NFAT reporter activity. Correspondingly, the levels of both nuclear NFATc1 and NFATc4 were constitutively elevated in IRAK-1 -/-cells. Furthermore, the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 31 publications
(39 reference statements)
2
28
0
Order By: Relevance
“…Abs against lamin B, b-actin, GAPDH, PPARa, RARa, C/EBPd, NF-kB-p65, and IkB kinase ε (IKKε) were purchased from Santa Cruz Biotechnology. The IkBa-specific Ab was obtained from Cell Signaling Technology, the anti-IRAK-1 Ab was obtained from Millipore, and the pFlag-IRAK-1 and various mutant IRAK-1 expression plasmids were generated as we described previously (12). The IKKε-specific inhibitor IX was purchased from Calbiochem.…”
Section: Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abs against lamin B, b-actin, GAPDH, PPARa, RARa, C/EBPd, NF-kB-p65, and IkB kinase ε (IKKε) were purchased from Santa Cruz Biotechnology. The IkBa-specific Ab was obtained from Cell Signaling Technology, the anti-IRAK-1 Ab was obtained from Millipore, and the pFlag-IRAK-1 and various mutant IRAK-1 expression plasmids were generated as we described previously (12). The IKKε-specific inhibitor IX was purchased from Calbiochem.…”
Section: Reagentsmentioning
confidence: 99%
“…Cell culture, transfection, immunoprecipitation, and Western blot analyses HeLa cells were cultured in complete BMDM medium, as previously described (12). Transfections with various IRAK-1 expression plasmids were performed using Lipofectamine reagents (Invitrogen), per the manufacturer's instruction.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IRAK-1 is constitutively active in blood mononuclear cells isolated from patients with atherosclerosis (23,29). Our recent study using ApoE Ϫ/Ϫ /IRAK-1 Ϫ/Ϫ mice also demonstrated that IRAK-1 deletion renders protection from high-fat diet-induced atherosclerosis (56). Despite compelling evidence linking IRAK-1 with the pathogenesis of atherosclerosis, the underlying molecular mechanism is not fully defined.…”
mentioning
confidence: 99%
“…In contrast, very limited information has been available regarding its function in macrophages, although NFAT is known to be expressed in these cells (41). We have previously reported that IRAK-1 is critically involved in maintaining NFAT in a phosphorylated and inactive state (56). IRAK-1 physically associates with NFAT and contributes to the phosphorylation of NFAT at its Ser-Pro-rich motif (56).…”
mentioning
confidence: 99%